Migration, diaspora, and information technology in global societies - Fortunati, Leopoldina (New York Routledge, 2012)
Migrants and diaspora communities are shaped by their use of information and communication technologies. This book explores the multifaceted role played by new media in the re-location of these groups of people, assisting them in their efforts to defeat nostalgia, construct new communities, and keep connected with their communities of origin. Furthermore, the book analyses the different ways in which migrants contribute, along with natives, in co-constructing contemporary societies ? a process in which the cultures of both groups are considered. Drawing on contributions from a range of disciplines including sociology, anthropology, psychology and linguistics, it offers a more profound understanding of one of the most significant phenomena of contemporary international societies ? the migration of nearly a billion people worldwide - and the relationship between technology and society.
Includes bibliographical references and index.
Keywords: Information technology--Social aspects